Dziga Vertov and Walt Whitman: Poetic Image in Documentary Films - K. L. Goryachok (Дискурс, 2022)
Introduction. The article is devoted to the little-studied issue of the influence of the American poet Walt Whitman on the work of the Soviet film director Dziga Vertov. The creative world of films and literary experiences of the documentary filmmaker is largely inspired by the images of American poet.Methodology and sources. On the basis of Vertov`s scripts, poems and archival documents, author analyzes the phenomenon of the director`s dialogue with Whitman and his poetry. In a comparative analysis of the aesthetics of the two artists, revealed that the philosophical ideas and imaginative system of the American poet were objects of artistic reflection on Vertov`s documentary films.Results and discussion. The article analyzes the leitmotifs of the work of Dziga Vertov, which, according to the author, were born under the great influence of the poetry of Walt Whitman. The imagery and ideas of the American poet`s works emerged in the director`s texts in the early 1920s. In his first manifestos Vertov introduced the image of an “electric man”, which in many ways correlates with the analogous one in Whitman`s lyrics. The author also points out that the Old Testament Adam appears in the texts and verses of Vertov under the direct influence of the American. The article examines the model of state and society in the works of Vertov and Whitman. The author finds similarities between the two artists in relation to the individual, the desire for equality and emancipation, the search for a spiritual principle in collectivism. The images of Lenin and Lincoln are analyzed separately. The semantic parallels between them in the poetics of the Vertov and Whitman are revealed and shows their direct comparisons in the genre, imagery and approaches.Conclusion. Analysis and comparison of images and motives of the work of Dziga Vertov and Walt Whitman allows to reveal new facets of the artistic world of the Soviet film director. The author notes that the ideological basis of his paintings often hid genuine creative intensions to search for intertextuality, to reveal the poetic image in documentary film.